2020
DOI: 10.1371/journal.pone.0236425
|View full text |Cite
|
Sign up to set email alerts
|

Condyle modeling stability, craniofacial asymmetry and ACTN3 genotypes: Contribution to TMD prevalence in a cohort of dentofacial deformities

Abstract: Craniofacial asymmetry, mandibular condylar modeling and temporomandibular joint disorders are common comorbidities of skeletally disproportionate malocclusions, but etiology of occurrence together is poorly understood. We compared asymmetry, condyle modeling stability and temporomandibular health in a cohort of 128 patients having orthodontics and orthognathic surgery to correct dentofacial deformity malocclusions. We also compared ACTN3 and ENPP1 genotypes for as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…Several studies reported the relation between TMJOA and craniofacial morphology [ 10 , 11 ]. Patients with TMJOA exhibited the retrusion and clockwise rotation of the mandible [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reported the relation between TMJOA and craniofacial morphology [ 10 , 11 ]. Patients with TMJOA exhibited the retrusion and clockwise rotation of the mandible [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…After the first selection, there were five human studies that met the above-mentioned requirements: two cross-sectional studies [13,18] and three case-control studies [11,19,20]. Four animal studies were also selected: one case-control study [16] and three experimental studies [21][22][23].…”
Section: Resultsmentioning
confidence: 99%
“…All authors used twodimensional radiographs for this purpose. Authors used different types of radiographs: Sofyanti et al [18,20] analysed asymmetry with panoramic radiograph and Chung et al [11] and Nicot et al [13] used cephalometric analysis. In article [19], Nicot et al performed diagnosis using different types of radiographs.…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%
See 2 more Smart Citations